Brodalumab in psoriasis: evidence to date and clinical potential - Amy C Foulkes; Richard B Warren (BioExcel Publishing Ltd, 2019)
Brodalumab is a recombinant, fully human monoclonal antibody (IgG2) which binds with high affinity to the interleukin (IL) 17 receptor A (IL17R). Brodalumab is now licensed and approved for the treatment of moderate-to-severe chronic plaque psoriasis in North America and Europe. As the third to market in the class of agents targeting IL-17, we review its place in the expanding armamentarium of cytokine-directed therapies for patients with severe psoriasis. Brodalumab is a highly efficacious therapy for psoriasis, whose mechanism of action is separate from other treatments targeting IL-17. Its use is associated with rapid control of the disease. We suggest that brodalumab is likely to be considered in those patients requiring rapid control of disease, where there is no known history of depression or suicidal ideation.